INTERRELATION OF COVID-19 AND HYPERTENSION; A REVIEW STUDY - Saleha Haidari; Zahra Rahimi; Sayed Muslim Musavi; Marina Hakimi (Scholar Express Journals, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a respiratory tract virus that causes Coronavirus disease (COVID-19). The virus originated in Wuhan, China, in December 2019 and has spread to the world. Most patients reported having at least one comorbidities with COVID-19 upon hospital admission. Hypertension, diabetes, chronic obstructive pulmonary disease, obesity, and cardiovascular diseases are among the most commonly reported. Comorbidities are contributing to acute disease prognosis and increased risk of severe symptoms. This review intends to understand how hypertension affect the disease’s prognosis and how severe the outcome can be expected
Keywords: SARS-CoV-2; Hypertension; RAAS inhibitors